1995
DOI: 10.1007/bf00182283
|View full text |Cite
|
Sign up to set email alerts
|

Lysine side-chain dynamics derived from 13C-multiplet NMR relaxation studies on di- and tripeptides

Abstract: 13C NMR relaxation data have been used to determine dipolar auto- and cross-correlation times for the di- and tripeptides GK, KG, and GKG, primarily to analyze lysine side-chain motional dynamics. In general, correlation times are largest for backbone positions and decrease on going through the lysine side chain, consistent with the idea of increased mobility at C delta and C episilon methylenes. Correlation times, however, vary with the peptide ionization state. In the zwitterionic state of GK, for example, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…4) as noted for V5 and G7. Because this tendency also has been observed for motions in a lysine side chain (Mikhailov et al, 1995), it may be that positive rotational correlations of adjacent bonds is the norm, at least in some structures. Daragan and Mayo (1996b) reported that, in P-strands, c$,$ rotations are positively correlated and, in this hairpin peptide, YIO is located within a /?-strand of a short P-sheet (Ramirez-Alvarado et al, 1996).…”
Section: Motions Of Tyrosine Y10mentioning
confidence: 59%
“…4) as noted for V5 and G7. Because this tendency also has been observed for motions in a lysine side chain (Mikhailov et al, 1995), it may be that positive rotational correlations of adjacent bonds is the norm, at least in some structures. Daragan and Mayo (1996b) reported that, in P-strands, c$,$ rotations are positively correlated and, in this hairpin peptide, YIO is located within a /?-strand of a short P-sheet (Ramirez-Alvarado et al, 1996).…”
Section: Motions Of Tyrosine Y10mentioning
confidence: 59%
“…Purification with flash column chromatography (hexane/EtOAc) yielded 12b as a yellow oil 24 mg (42%). IR (Nujol) ν max 2970 cm -1 , 2920 cm (22), 166 (64), 83 (51), 67 (42), 55(53), 41(100).…”
Section: Synthesis Of V(h) (4b Scheme 1) (A) 1-oxyl-trans-3-(methylsu...mentioning
confidence: 99%
“…The meaning of the best-fit order parameters S f 2 extracted from fits using the LS-2 and -3 models in cases where slow side-chain dynamics is present is discussed below. Theoretical treatments which draw the connection between the model-free parameters and more fundamental quantities describing side-chain torsional dynamics have been presented in a number of recent papers. …”
Section: Model-free Approaches To Analysis Of Spectral Densitiesmentioning
confidence: 99%